The dynamics of surface boundary layer during total Solar eclipse 1995 - ARULRAJ, S.; DHARMARAJ, T.; DEBAJE, S. B.; SINGH , A. BAGAVATH; VERNEKAR, K. G. (MAUSAM, 1998)
A microclimatological tower of 1.6 m height with six instrumented booms at different heights carrying wind speed, temperature and humidity sensors was set up at Robertsgun 24° 42'N, 83°4'E, 3l2m amsl) to study the implication of the total Solar eclipse on the dynamics of Atmospheric Boundary Layer (ABL). Apart from this, the soil temperature and heat flux were also measured during the same time. The observations were taken with a one minute average interval and recorded continuously with the data logger and then transferred to a PC for later use. The data were collected during 2l –26 October 1995. During the eclipse period decrease of surface temperature and soil temperature by 6.2°C and 3.5°C respectively and increase of humidity by nearly 60% were observed. Due to the decrease in velocity fluctuations, the mean wind speed showed the sharp increase compared to other days. The setting of stable atmosphere before the total solar eclipse was observed.